THE EFFECTIVENESS OF NUMBERED HEADS TOGETHER IN SPEAKING SKILLS OF RECOUNT TEXT AT EIGHTH GRADE STUDENTS IN MTS ANNUR BAITURRAHIM SEPPONG - Irmayanti, irmayanti (English Edu: Journal of English Teaching and Learning, 2023)
ABSTRACT The purpose of this research was to find out whether the use of numbered heads together was effective in speaking skills in recount text for class VIII students at MTS Annur Baiturrahim Seppong. In this research, researcher used a quantitative research approach with the pre-experiment research method and the design used was one group pretest and posttest design. The samples of this research were ten students in class VIII consisting of six males and four females. Instrument in this research was an oral test. The results of the students' pretest and posttest obtained would be calculated and analyzed use SPSS 21. The results of this research, that score was obtained by students from pretest to posttest showed that posttest result was higher than pretest. The highest score on the pretest was 68, while the lowest score was 48. With an average value = 55.9, standard deviation was 7.156 as well standard error was 2.263. While the highest score on the posttest was 85 and the lowest score was 62, the average value was 71.2, standard deviation was 7.33 and the standard value error was 2,318. Next, the results of the hypothesis test used sample paired t-test which shows that the t table was lower than the t value was 2.262˂25.619. It means that the alternative hypothesis was accepted and the null hypothesis was rejected. Keywords: Numbered Heads Together; Speaking Skills; Recount Text ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui apakah penggunaan numbered heads together efektif dalam kemampuan berbicara pada recount text siswa kelas VIII di MTS Annur Baiturrahim Seppong. Dalam penelitian ini, peneliti menggunakan pendekatan penelitian kuantitatif dengan metode penelitian pre-experiment serta desain yang digunakan adalah one group pretest and posttest. Jumlah sampel yang digunakan dalam penelitian ini, adalah sebanyak sepuluh siswa kelas VIII yang terdiri dari 6 laki-laki dan 4 perempuan. Instrumen yang digunakan dalam penelitian ini adalah tes lisan. Hasil dari pretest dan posttest siswa yang diperoleh akan dihitung dan dianalisa menggunakan bantuan SPSS 21. Hasil dari penelitian ini, menunjukkan bahwa hasil postest lebih tinggi daripada pretest. Skor tertinggi pada pretest adalah 68, adapun skor terendahnya adalah 48. Dengan nilai rata-rata = 55.9, standart deviasinya adalah 7.156 serta standart erornya adalah 2.263. Sedangkan skor tertinggi pada posttest adalah 85 dan skor terendah adalah 62, nilai rata-ratanya adalah 71.2, standart deviasinya adalah 7.33 serta nilai standar eror adalah 2.318. Selanjutnya, hasil dari uji hipotesis menggunakan sample paired t-test yang menunjukkan bahwa t table lebih rendah dari nilai t yaitu 2.262˂25.619. Ini berarti bahwa hipotesis alternatif diterima dan hipotesis nol ditolak. Kata-Kata Kunci: Numbered Heads Together; Kemampuan Berbicara; Teks Recount